Aerospace series. Connectors, electrical, circular, coupled by threaded ring, fire resistant or non fire resistant, operating temperatures -65 °C to 175 °C continuous, 200 °C continuous, 260 °C peak. Dummy receptacle. Product standard Part 011, (17th December 2019) - British Standards Institution,
No abstract available